2016
DOI: 10.1038/srep21946
|View full text |Cite
|
Sign up to set email alerts
|

A method to study electronic transport properties of molecular junction: one-dimension transmission combined with three-dimension correction approximation (OTCTCA)

Abstract: Based on the ab initio calculation, a method of one-dimension transmission combined with three-dimension correction approximation (OTCTCA) is developed to investigate electron-transport properties of molecular junctions. The method considers that the functional molecule provides a spatial distribution of effective potential field for the electronic transport. The electrons are injected from one electrode by bias voltage, then transmit through the potential field around the functional molecule, at last are pour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 58 publications
(78 reference statements)
1
18
0
Order By: Relevance
“…Note that Eq. ( 3) also displays an exponential dependence of the molecular junction resistance on total molecular lengths which is in agreement with observations made by others [26][30] [32].…”
Section: Bottom Electrodesupporting
confidence: 91%
See 1 more Smart Citation
“…Note that Eq. ( 3) also displays an exponential dependence of the molecular junction resistance on total molecular lengths which is in agreement with observations made by others [26][30] [32].…”
Section: Bottom Electrodesupporting
confidence: 91%
“…Using a combination of the non-equilibrium Green's function, Density functional theory (DFT), and confirmed I-V characteristics, Ratner 38 concluded that the degree of conjugation and overlap of the orbital densities of the molecular end group and the contact electrodes together determine the heightened conductivity of these molecular chains because of constant delocalized charge transport. Alkane diamine molecules have also been studied using common computational chemistry algorithms 39 , where the length dependence of the electrical conductance has been observed to be exponential, similar to thiol linker molecules. Generally, most organic molecules demonstrate an exponential dependence of the electrical properties on the molecule length.…”
Section: Thiol Sam Capture Layermentioning
confidence: 99%
“…33,44 The stretch-induced change in geometry greatly reduces the interaction between the π orbitals of BPY and the Au electronic states because the interaction between the π orbitals and Au electronic states is more direct in the case of BPY molecules than in the case of BDT molecules (Figure 4b). 30,41 Therefore, the electronic states in which π orbitals on the benzene ring are decoupled to p orbitals on S atoms in the SMJ lead to tolerance of the coupling to the stretching at the expense of the coupling of the initial states. In the present study, we have investigated metal−molecule interactions using a combination of I−V curves and SERS spectra at SMJs.…”
mentioning
confidence: 99%
“…To consider the contact properties of the thiol anchor, , we compared the observed response of BDT with that of BPY. Figure d,e shows plots of the stretch dependence of the coupling and the relative change of the CC stretching mode for both the BDT and BPY molecules.…”
mentioning
confidence: 99%
“…B f is the single-point energy of the final configuration (here, the single-point energy of the initial configuration is set as zero). Considering that B ( x ) is irregular, we solve eq numerically using the numerical method introduced in the literature . Then, the reflected coefficient R is obtained, and furthermore, the configuration conversion probability is derived by P = | S | 2 = 1 – | R | 2 .…”
Section: Theoretical Models and Computational Detailsmentioning
confidence: 99%